The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1300/j001v26n01_13
|View full text |Cite
|
Sign up to set email alerts
|

Supervision of Lesbian, Gay, and Bisexual Social Work Students by Heterosexual Field Instructors

Abstract: This paper describes findings from a qualitative study of lesbian, gay, and bisexual (LGB) student-heterosexual field instructor dyads. Each dyad was assessed for its level of agreement in characterizing the student's experience in field placement. Disagreements were common, with more than half of the dyads having 2-5 areas of disagreement. The following factors seemed to impact the level of student-field instructor agreement: the field instructor supervisory style, the quality of the studentfield instructor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
(14 reference statements)
2
19
0
Order By: Relevance
“…In a follow-up study by Newman et al (2009), field instructors supported this finding and noted that trainees comfort level in disclosing their sexual orientation affected trainees "ability to engage effectively and in a professional manner with clients" (p.11). These findings confirm previous studies in the social work literature that identified feelings of lack of safety and affirmation as a major obstacle in the training experiences of LGB trainees (Messinger, 2004(Messinger, , 2007.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…In a follow-up study by Newman et al (2009), field instructors supported this finding and noted that trainees comfort level in disclosing their sexual orientation affected trainees "ability to engage effectively and in a professional manner with clients" (p.11). These findings confirm previous studies in the social work literature that identified feelings of lack of safety and affirmation as a major obstacle in the training experiences of LGB trainees (Messinger, 2004(Messinger, , 2007.…”
supporting
confidence: 91%
“…In a follow-up study by Newman et al (2009), field instructors supported this finding and noted that trainees comfort level in disclosing their sexual orientation affected trainees "ability to engage effectively and in a professional manner with clients" (p.11). These findings confirm previous studies in the social work literature that identified feelings of lack of safety and affirmation as a major obstacle in the training experiences of LGB trainees (Messinger, 2004(Messinger, , 2007.Long (1997, 2002) suggests that LGB supervisees are often concerned about the ramifications their sexual orientation on their training. She also contends that LGB supervisees may face additional challenges within supervision, including lack of acceptance by supervisors and other supervisees, becoming silenced by their marginalized status, and the responsibility of educating supervisors and supervisees about heterosexist bias and homophobia in order to create a more affirmative supervision environment.…”
supporting
confidence: 88%
See 3 more Smart Citations